2011
DOI: 10.1016/j.socscimed.2010.09.053
|View full text |Cite
|
Sign up to set email alerts
|

Family medicine, ‘La Herencia’ and breast cancer; understanding the (dis)continuities of predictive genetics in Cuba

Abstract: Building on social science research examining the relationship between genetic knowledge, identity and the family this paper takes the cultural context of Cuba as a site for critical ethnographic engagement. The paper makes use of research working with a range of Cuban publics and genetic professionals as part of a collaborative research project exploring the social and cultural context of health beliefs about breast cancer. It illuminates the contrasting ways in which genomic knowledge linked to an increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 20 publications
0
15
0
2
Order By: Relevance
“…Literature on Latinos' awareness and understanding of family health history and its relationship to disease risk is limited, with almost no research on recent immigrants who live outside of urban centers. There is some evidence suggesting that Latinos are aware that family health history can be a risk factor for disease and are familiar with family health history information being requested during health care interactions (Gibbon 2011;Vadaparampil et al 2010). But, studies have also shown that the active collection of family health history within Latino families is rare (Centers for Disease Control 2004;Corona et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature on Latinos' awareness and understanding of family health history and its relationship to disease risk is limited, with almost no research on recent immigrants who live outside of urban centers. There is some evidence suggesting that Latinos are aware that family health history can be a risk factor for disease and are familiar with family health history information being requested during health care interactions (Gibbon 2011;Vadaparampil et al 2010). But, studies have also shown that the active collection of family health history within Latino families is rare (Centers for Disease Control 2004;Corona et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The literature indicates that Latinos, particularly those from underserved communities, may not recognize that family health history is related to genetics (Ricker et al 2007). Additionally, multiple studies have shown that Latino community members often have limited awareness and understanding of issues related to inherited risk for disease (Gibbon 2011;Kaphingst et al 2011;Kinney et al 2010;Vadaparampil et al 2010). Latinos may also not understand risk in a genetic context because of limited genetic literacy, defined as the capacity to obtain, process, understand, and use genetic information (Eichmeyer et al, 2005;Lea et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…46,48,67,74,76,77,81,103,119,144,[151][152][153][154][155][156] Patients are hesitant to disclose their genetic results to extended family and community, and many experience social isolation after such disclosure. 76,77,81,103,134,152,155 Affected individuals and their families experience discrimination when seeking marriage prospects. 48,57,81,103,134,154 The negative portrayal of genetic diseases in the media (e.g., "children who should not have been born") is a significant factor contributing to stigma.…”
Section: Ethical Issuesmentioning
confidence: 99%
“…Testes genéticos para o câncer de mama hereditário, por exemplo, podem criar graus de ansiedade difíceis de serem resolvidos. No caso de resultados positivos que aumentam o risco para este tipo de câncer, a solução apresentada passa muitas vezes pela retirada preventiva das mamas, uma decisão complexa e nem sempre acessível para todas as mulheres 20,21 . Além disso, a disseminação desses testes poderia vir a formar uma nova classe de pessoas estigmatizadas: os doentes pré-sintomáticos, pessoas que são completamente saudáveis, mas cujos testes genéticos apontam para possibilidade de desenvolverem uma doença no futuro.…”
Section: Família E Sofrimentos De Longa Duraçãounclassified